A theoretical and descriptive comparison of stock purification methods : profit based and income based - Ünver, Hayrullah Sabri (My University, 2025)
Bu çalışmada hisse senedi arındırma yöntemleri kara dayalı ve gelire dayalı yöntemler olmak üzere iki başlık altında incelenmiştir. Her iki yöntemi tavsiye eden kurumlardan bahsedilmiştir. Arındırma yöntemlerinin gerçek verilere uygulandığında gösterdiği sonuçların incelenebilmesi için BIST katılım 100 endeksinden hesaplanama için elverişli verisi olan 69 şirketin 2022-2024 yılları arası üç yıllık arındırma tutarları her iki yönteme göre hesaplanmış ve karşılaştırılmıştır. Çalışmada ana çıktı olarak bu 69 şirketin toplam arındırma tutarları hesaplanmıştır. Ek olarak arındırma oran ve tutarlarının hangi makroekonomik değişkenlerden etkilendiği, farklı sektörlerde nasıl değişiklik gösterdiği, yatırımcı kâr veya zarar ettiği durumlarda arındırmanın gerekli olup olmadığı incelenmiştir. Çalışmada ortaya koyulan en önemli bulgular gelire dayalı arındırma yönteminin kâra dayalı yönteme göre çok daha fazla tutarda arındırma yapmayı gerektirmesi ve şirketlerin katılım finansına uygun olmayan gelir oranlarının reel faiz arttıkça arttığının gösterilmesidir.

In this study, stock purification methods are examined under two main categories: profit-based and income-based methods. The institutions recommending each approach are discussed. In order to examine the results of applying purification methods to real data, the three-year purification amounts of 69 companies in the BIST Participation 100 Index, for which the data was available for calculation, were computed for the years 2022–2024 according to both methods and compared. As the main output of the study, the total purification amounts of these 69 companies were calculated. Furthermore, the study investigates which macroeconomic variables influence the purification ratios and amounts, how these figures vary across different sectors, and whether purification is required when investors make profits or incur losses. The most significant findings of the study are that the income-based method requires substantially higher purification amounts compared to the profit-based method, and that the ratio of Shariah non-compliant income increases as the real interest rate rises.
Kâra dayalı ve gelire dayalı hisse senedi arındırma yöntemlerinin teorik ve betimsel karşılaştırması
Keywords: Bankalar ve bankacılık; Banks and banking; Dini yönler; Dini yönleri; Finance; Finans; Gelire Dayalı Arındırma Islamic Indices; Hisse Senedi Arındırması; Income-Based; Islam; İslam; İslami; İslami Endeksler; Kâra Dayalı Arındırma; Law and legislation; Menkul değerler borsası; Profit-Based Purification; Purification; Religious aspects; Stock exchanges; Stock Purification; Turkey; Tü; Yasa ve yasama